THE ROLE OF INTERNATIONAL LEGAL INSTRUMENTS IN THE FORMATION OF A SECURITY ENVIRONMENT - Vladyslav Hrichanichenko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
The article draws attention to the existence of an urgent need to reform all spheres of life and functioning of the state, which will contribute to the formation of a safe environment. The issues of this issue become especially relevant after the full-scale invasion of the territory of Ukraine on February 24, 2022, which is due to the complexity of the international situation of our country, the conduct of active hostilities, the spread of international terrorism, the aggravation of threats to the interests of individual citizens, society and the state as a whole, which requires the development effective measures to ensure national security